2022
DOI: 10.1038/s41398-022-01947-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pharmacological treatment on metabolomic alterations in animal models of depression

Abstract: Numerous studies have investigated metabolite alterations resulting from pharmacological treatment in depression models although few quantitative studies explored metabolites exhibiting constant alterations. This study aimed to identify consistently dysregulated metabolites across such studies using a knowledgebase-driven approach. This study was based on 157 studies that identified an assembly of 2757 differential metabolites in the brain, blood, urine, liver, and feces samples of depression models with pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 70 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…The effects of CUMS, HCW and HCE on the composition and function of the intestinal flora were analyzed via 16S rRNA sequencing. The community composition was analyzed to obtain the abundance and diversity of each species ( Pu et al, 2022 ). At the phylum level, Firmicutes , Bacteroidetes , and Proteobacteria were predominant in all samples but varied in their abundances ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of CUMS, HCW and HCE on the composition and function of the intestinal flora were analyzed via 16S rRNA sequencing. The community composition was analyzed to obtain the abundance and diversity of each species ( Pu et al, 2022 ). At the phylum level, Firmicutes , Bacteroidetes , and Proteobacteria were predominant in all samples but varied in their abundances ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that 5-HIAA can be decomposed by serotonin intracellular monoamine oxidase (MAO), and both metabolites are closely related to depression and are expressed at low levels in patients with depression [67,68]. In addition, cortisol plays several key roles in promoting homeostasis, including regulating and suppressing healthy stress responses [69].…”
Section: Plos Onementioning
confidence: 99%
“…Similar to other studies [ 12 , 13 ], our earlier research [ 14 ] found that though there was no significant difference in high-density lipoprotein cholesterol (HDL-C) and triglyceride (TG) between the MDD patients and healthy controls (HCs), the total cholesterol (TC) and LDL-C levels were much lower in MDD compared to HCs. Meanwhile, the TC levels were positively correlated with LDL-C levels, and the reduction of TC was connected with the severity of MDD [ 9 ], suggesting that low lipid levels may play a role in the pathogenesis of MDD. In addition, the absence of a specific molecular basis for diagnosis in psychiatry at this time prevents the creation of diagnostic tools, and diagnosis in MDD is still reliant on symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 30-40% remit with antidepressant treatment leaving nearly 60-70% of patients who do not optimally respond [7]. Increased knowledge suggested that lipid abnormalities play a significant part in the pathophysiology of MDD [8][9][10][11], which may open up a new avenue for research into the underlying mechanism of MDD.…”
Section: Introductionmentioning
confidence: 99%